A human-centric participatory approach to energy-efficient housing based on occupants' collaborative image. Issue 4 (16th June 2021) - Asad Poor, Javad; Goh, Yong Wah; Thorpe, David
Abstract : Purpose: This study aims to develop a photo-based methodology to identify occupants' collaborative image of the energy-efficient small-size housing. Design/methodology/approach: Employing qualitative and quantitative approaches, 24 photos were randomly selected from different urban areas of Brisbane (Australia) city for an online survey. A total of 36 participants evaluated the photos 159 times. Findings: Conducted content analysis resulted in the identification of 5 attribute-based factors, generated from 16 semantic categories and 74 attributes. Using a non-parametric Chi-square test, the factors were categorised in two levels, i.e. (1) envelope elements (primary and secondary) and passive climatic principles; and (2) architectural composition principles and neighbourhood quality. Social implications: The discussion on the results via the theory of planned behaviour (TPB) suggests that regarding the external aspects, the people's image of energy-efficient housing could be influenced by their perceived control over changeable and adjustable attributes. Originality/value: The photo-based methodology developed by this paper has the potential to quantify occupants' collaborative image of small-size housing energy efficiency, which would be essential in assisting them to adjust their dwelling units regarding the congruity of the energy efficiency attributes with their preferences.